Laporan Kasus: Kajian Efek Samping Obat Antipsikotik pada Kejadian Gejala Ekstrapiramidal pada Pasien Skizofrenia - Madury, Shalahuddin Al Madury; Padmasari, Siwi; Ishak, Ishak (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2024)
Background: Initial treatment of acute psychosis in schizophrenia patients is recommended to start second-generation antipsychotics rather than first-generation antipsychotics which have greater side effects on movement disorders, such as akathisia, and dystonia. Extrapyramidal symptoms (EPS) are one of the most common side effects of drugs experienced by patients due to dopamine receptor blocking agents in the form of uncontrolled movements that risk disrupting patient activities. Objective: The purpose of this case report is to determine the pattern of antipsychotic drug use, and the results of a clinical pharmacist study related to the side effects of drugs causing EPS in schizophrenia patients in the inpatient installation of Soerojo Hospital. Method: This study is in the form of a case report taken from an inpatient of Soerojo Hospital in Magelang City. Case data were collected through various methods during the pharmacist's visit, all patient-related data were recorded and a comprehensive assessment was carried out to see the suitability of therapy, DRP in patients by comparing it with existing literature. Result: Patient NH (18 years old) was diagnosed with Schizophrenia for the first time. The patient received Diazepam and haloperidol injection therapy while in the ER and was programmed with haloperidol 5 mg every 12 hours, and clozapine 100 mg 2x a day, on the third day the patient could not swallow the medicine because he showed symptoms of EPS such as stiffness, mouth could not close, walking like a robot, and hypersalivation. Pharmacists through pharmaceutical care found DRP related to potential ESO from the use of haloperidol injection which increased the incidence of EPS, especially in patients who first received antipsychotics. 2 days later, signs of EPS continued to NMS marked by severe hypersalivation, rigidity, and muscle stiffness disorders, and supported by high CK examination results of 2030 U / l. The patient received Trihexyphenidyl therapy 3x2 mg, and bromocriptine 2.5 mg / 8 hours. Slowly the symptoms of NMS experienced clinical improvement. Conclusion: Early discontinuation of antipsychotic agents that cause EPS can prevent the severity of EPS in patients. Bromocriptine can be an option for NMS patients.